The Impact of Using Paper Dictionaries in Exams on Iraqi Student Translators’ Translation Quality - Al-Maryani, Jasim; Al-Dirawi, Afaneen (Al-Adab Journal, 2025)
Bilingual paper dictionaries are very useful in translation.  However, they can also be tricky, because they do not provide definitions and are restricted to indefinite equivalents. This means that when searching for a word in the source, there are often some possible alternatives. The difficulty arises for those unaware of the adequate operation of the different equivalents in the target language, or how to associate them in terms of structures. This is the problem that many Iraqi student translators encounter as they are not competent enough to decide the most acceptable alternative. Therefore, they spend much of the exam time translating individual words, i.e., their overall product lacks cohesiveness.  This absence of the systemic approach they can follow in the exams can negatively contribute to the quality of their translations. The present paper addresses such a problem with special reference to literary discourse. Like AlFayez (2023), it encourages a hybrid approach, one that allows the use of paper dictionaries, but with a crucial modification in the procedure; dictionaries are allowed only in the first third not the first half of the exam allocated time. After that, dictionaries are withdrawn, and trainees have to complete their assignments depending on their knowledge. Results indicated that translations produced according to the first third of the allocated time approach are more cohesive, accurate, and stylistically appropriate than those relying on dictionaries for half the time. The findings underscore the significance of time management and efficient dictionary usage in achieving high-quality translations, emphasizing that excessive reliance on dictionaries can impede coherence and overall translation quality.